2022
DOI: 10.3389/fendo.2021.770824
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Microcarcinoma: A Nomogram Based on Clinical and Ultrasound Features to Improve the Prediction of Lymph Node Metastases in the Central Compartment

Abstract: BackgroundAccurate preoperative identification of central lymph node metastasis (CLNM) is essential for surgical protocol establishment for patients with papillary thyroid microcarcinoma (PTMC). We aimed to develop a clinical and ultrasound characteristics-based nomogram for predicting CLNM.MethodsOur study included 399 patients who were pathologically diagnosed with PTMC between January 2011 and June 2018. Clinical and ultrasound features were collected for univariate and multivariate analyses to determine ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Nevertheless, men are more likely to develop CNLNM once their immune defenses have been breached. The male sex was believed to be an independent risk factor in the previous research (20)(21)(22)(23). However, the differences in the extent of thyroid cancer in men versus women may not only be related to biological factors.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, men are more likely to develop CNLNM once their immune defenses have been breached. The male sex was believed to be an independent risk factor in the previous research (20)(21)(22)(23). However, the differences in the extent of thyroid cancer in men versus women may not only be related to biological factors.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies concluded that tumor size ≥1 cm is more likely to develop CNLNM than tumor size <1 cm ( 20 22 ), although several studies have not segmented tumors by 1 cm ( 23 29 ), and some studies concluded that larger tumor volume is more likely to develop CNLNM ( 30 , 31 ). In sum, CNLNM is generally more likely to occur with larger tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex, age, and tumor size are considered as risk factors for lymph node metastasis in PTMC patients ( 29 , 30 , 31 ). Our results showed that the RFS was comparable between male and female PTMC patients, although most of the recruited patients were women.…”
Section: Discussionmentioning
confidence: 99%
“…Today, many prediction models have been established and applied to TC, but mainly for poor prognostic histological types such as ATC and MTC. The study population is also dominated by middle-aged and children [ [19] , [20] , [21] ]. However, for the middle-aged group with the highest incidence of PTC and long life expectancy, there is still no effective and reliable nomogram to predict prognosis.…”
Section: Introductionmentioning
confidence: 99%